Determinants of reinsurance costs for Turkish non-life insurance companies - Alan, Burak (My University, 2019)
Bu tezde, sigorta sözleşmesi riskini paylaşmak için sigorta şirketinin ödediği para olan reasürans maliyeti ile sigorta şirketleri için iyi izleme araçları olan finansal ve teknik oranlar arasında bir ilişki bulunması amaçlanmaktadır. Bu tez, reasürans hakkında fikir vermek umuduyla yazılmıştır. Reasürans maliyeti ve finansal ve teknik oranlarla arasındaki ilişkisi kurulmuş ve ampirik bir sonuç elde etmek için panel veri regresyonu yapılmıştır. Bu çalışmayı yaparken TSB’nin resmi internet sitesinden elde edilen verilerden yararlanılmıştır. Bu veriler, toplam 27 şirketin dokuz yılını (2009 – 2017) içermektedir. Bu tezde reasürans maliyetlerinın belirleyicilerinin bulunmasına dair hipotezler test edilmiştir.

In this thesis, it was aimed to find a relationship between reinsurance cost which is the money paid by the insurance company to share the risk of insurance contract and financial and technical ratios which are good monitoring tools for insurance companies. This thesis was written in the hope of giving an idea about reinsurance. The relationship between reinsurance cost and financial and technical ratios was established and panel data regression was performed to obtain an empirical result. The data obtained from the official website of the IAT was used in this study. This data includes nine years of the total 27 non-life companies (2009 - 2017). Hypotheses have been tested to find the determinants of the reinsurance cost.
Keywords: Insurance; Insurance companies; Rasyo; Ratio; Reasürans; Reasürans Maliyeti; Reinsurance; Sigorta Reinsurance Cost; Sigorta şirketleri; Turkey; Türkiye